Sobre la tradición documental. Un documento singular de San Isidoro de León - Martín López, María Encarnación (Estudios humanísticos. Geografía, historia y arte, 1994)
In this paper, we restate the problems of documentary tradition by examinig the controversial case which we found in the archives of the Collegiate of San Isidoro in León under the catalogue number 365. It is an indenture dated in 1212, the content of which is a donation given to the above mentioned monastery in the year 1198. It is the aim of our survey to establish that it is a copy, against the criteria of other authors who classify it as original.